Race-Related Disparities in 5-Year Cognitive Level and Change in Untrained Active Participants. (December 2013) - Marsiske, Michael; Dzierzewski, Joseph M.; Thomas, Kelsey R.; Kasten, Linda; Jones, Richard N.; Johnson, Kathy E.; Willis, Sherry L.; Whitfield, Keith E.; Ball, Karlene K.; Rebok, George W.
Objective: The current study examined a 5-year cognitive change in untrained African American and White participants from the Advanced Cognitive Training in Independent and Vital Elderly (ACTIVE) study.Method : Five-year trajectories of memory, reasoning, visual processing speed/useful field of view, digit-symbol substitution, and vocabulary were investigated. Education, health, gender, age, and retest/practice effects were controlled for, and a missing data pattern mixture approach was used to adjust for dropout effects.Results : After considering age, education, health, and gender, being African American uniquely explained 2% to 7% of the variance in cognitive performance. There were virtually no significant race differences in the rates of change.Discussion : Race-related results in the current study are consistent with previous research suggesting that social advantage factors such as education have a stronger influence on the level of performance than the rate of change. The small remaining effects of being African American on performance levels likely reflect uncontrolled variation in factors like literacy and financial advantage.